Penggunaan Teleskop: Kesan Terhadap Hukum Ithbat Kenampakan Anak Bulan di Malaysia - Nizam, Nurul Kausar; Mohd Nawawi, Mohd Saiful Anwar; Abdul Niri, Mohammaddin; Man, Saadan; Zainuddin, Mohd Zambri (Jurnal Fiqh, 2014)
Observation of the lunar crescent is quite challenging, as it is influenced by various dynamic factors, particularly local and atmospheric conditions. The adoption of astronomical methods and instrumentation, such as the telescope and imaging technique using a digital single lens reflex camera (DSLR), undeniably provide better results than unaided observation. However, the results from aided observation are debated by some Muslim jurists, and, therefore, this paper attempts to analyse the adoption and its results from the fiqh perspective and astronomical considerations. Astronomical data were taken at Teluk Kemang Negeri Sembilan, Malaysia. This study found that the adoption has its own fiqh justification and is still consistent with the criteria of Imkan al-Ru’yah.